Analisis Strategi Pemasaran Untuk Meningkatkan Daya Saing UMKM Kota Jambi - Efandri Agustian; Indah Mutiara; A Rozi (Universitas Batanghari, 2020)
The development of information and technology causes fierce business competition, causing micro, small and medium enterprises (MSMEs) to be able to survive and compete for market share by implementing strategies, concepts and good management designs. Management is the key factor for success in the era of technology and information nowadays in order to create opportunities for its products. The purpose of this study is to determine the strengths, weaknesses, opportunities and threats, to compile IFAS (Internal Factor Analysis Summer) and EFAS (External Factor Analysis Summer) and to find out a good marketing strategy after analyzing with SWOT (Strength, Weakness, Opportunity, Threat). The phenomenon that exists, MSME entrepreneurs facing fierce competition is marked by the proliferation of products from outside the region. This study uses the SWOT analysis method to identify the company's internal and external factors. The data were collected through observation, interviews, and distribution of questionnaires to MSME entrepreneurs. The results of these studies as follow: (1) the results of the IFAS analysis are 4.00 that the position is very profitable for the company, in which the strongest factor in the internal company is guaranteed product quality. (2) The results of the EFAS analysis obtained a score of 2.66, in which this position is medium from the external factors of the company, in other words, there are still many companies that supposed to extend optimize opportunities to minimize existing threats. (3) The IE matrix results show the current average position of MSMEs in Quadrant 1, this is very profitable situation in which the company has excellent opportunities and strengths. The strategy that should be applied in this condition is to support policies development through activities: documentation, interviews and observations. The data analysis technique used content analysis (research documentation) and descriptive analysis.